2014
DOI: 10.1080/10590501.2014.967061
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention Against Arsenic-Induced Mutagenic DNA Breakage and Apoptotic Liver Damage in Rat Via Antioxidant and SOD1 Upregulation by Green Tea (Camellia sinensis) which Recovers Broken DNA Resulted from Arsenic-H2O2Related in Vitro Oxidant Stress

Abstract: Green tea (Camellia sinensis; CS) strongly reverses/prevents arsenic-induced apoptotic hepatic degeneration/micronecrosis and mutagenic DNA damage in in vitro oxidant stress model and in rat as shown by comet assay and histoarchitecture (HE and PAS staining) results. Earlier, we demonstrated a link between carcinogenesis and impaired antioxidant system-associated mutagenic DNA damage in arsenic-exposed human. In this study, arsenic-induced (0.6 ppm/100 g body weight/day for 28 days) impairment of cytosolic sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Earlier our laboratory has demonstrated the anti-carcinogenic role of green tea extract [13,14]. It decisively helps in DNA protections by scavenging free radicals and that efficacy was found to be even greater than the known specific radical-scavengers [14,15]. According to the relationships between structure and antiviral activity of catechin derivatives, the 3-galloyl and 5′-OH group of catechin derivatives appear critical to antiviral activities [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier our laboratory has demonstrated the anti-carcinogenic role of green tea extract [13,14]. It decisively helps in DNA protections by scavenging free radicals and that efficacy was found to be even greater than the known specific radical-scavengers [14,15]. According to the relationships between structure and antiviral activity of catechin derivatives, the 3-galloyl and 5′-OH group of catechin derivatives appear critical to antiviral activities [22].…”
Section: Resultsmentioning
confidence: 99%
“…Tea flavonoids have been demonstrated as strong anti-toxicant, anti-oxidant and anti-inflammatory agents. Anti-tumerigenic role of catechin derivatives especially EGCG has been shown decisively by several laboratories [13,14,15]. Regarding the anti-viral role tea flavonoids have been shown to be strong agent [16].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant treatments have been reported to enhance the antioxidative capacity of these enzymes [57,122]. Recently, Acharyya et al [141] have shown upregulation of SOD and CAT activities by green tea extract in rats as well as in vitro using rat liver cells. They also showed that green tea extract was effective in the prevention of arsenic-induced hepatic tissue and DNA damage via restoration of arsenic-depleted hepatic xanthine oxidase (XO) and serum uric acid levels.…”
Section: Protective Mechanism Of Antioxidants Against Arsenic Genotoxmentioning
confidence: 99%
“…The beneficial effects of green tea on arsenic-associated toxicities were summarized in Table 5 [117130]. Green tea and its principal polyphenol, (−)-EGCG, efficiently counteracted the cytotoxic effects of arsenic compounds in Chinese hamster lung fibroblast V69 cells [128].…”
Section: Green Tea Modulates Arsenic-associated Toxicities and Cancermentioning
confidence: 99%
“…GTE reduced arsenic-induced formation of 8OHdG and induced arsenic-suppressed DNA repair enzymes, such as PARP1, DNA β-polymerase, XRCC1, DNA ligase III, DNA protein kinase (catalytic subunit), XRCC 4, DNA ligase IV, and DNA topoisomerase Iiβ, in Swiss albino mice [127]. GTE (≥10 mg/ml aqueous) restored arsenic-induced mutagenic DNA breaks and liver damages in rats via upregulation of cytosolic SOD [117]. Similarly, supplementation of tea extracts (10 mg/mL water) with NaAsO2 (0.6 ppm)/100 g b.w.…”
Section: Green Tea Modulates Arsenic-associated Toxicities and Cancermentioning
confidence: 99%